Une statue de togatus découverte dans l’agglomération antique de Briord (Ain) - Thomas Le Saint Quinio; Maria-Pia Darblade-Audoin (Gallia)
A togatus, dating to the first part of the 1st c. AD, was discovered, in proximity to a Roman road, during the archaeological survey of an urban district of Briord (Ain).This discovery sheds new light on the Roman centre of Briord, located between Lyon and Geneve, on the right bank of the river Rhône, and at the border of Vienne and the Allobroges civitas. Briord was not a well-known city, but the recent archaeological efforts revealed an important throughway functioning in Antiquity (1st-3rd c. AD) and early outlines of other routes, as well as an important necropolis in the north, and a bathhouse (2nd c. AD). An inscription provides us with the name of the village: Brioratis, [Br]ioratenses (CIL XIII, 2464 ; ILAin, 2005, 28). Unfortunately, the information provided is not precise enough to draft a map of the township in Antiquity, but generally speaking, it appears to correspond well to an overlay of the modern plan of the church’s perimeter. The major public buildings have yet to be discovered, but some large substructures had been located near the church. A cult of Mercury is attested to by the discovery of a bronze statuette, an altar (CIL XIII, 2461 ; ILAin 2005, 24) and a gift of a proscaenium to the god (CIL XIII, 2462 ; ILAin 2005, 25).The Roman road that crosses Briord measures eight metres in width and was used since the beginning of the 1st c. to the end of the 3rd c. AD. The preliminary excavation focused on an urban district named “rue Saint-Didier, Les Ecolus”. The trench where the statue was discovered was located along the edge of the road. This layer was composed of a deep layer of coal dust mixed with scraps of metal and ceramics (dated to 27 BC-60 AD) and which was covered by a thick layer of a backfill. The latter was comprised of vestiges belonging to demolition phases, including the statue, some large limestone blocks and other, smaller fragments of lime. The second excavation, performed in 2020 provided us with further architectural clues regarding a funerary monument (E. Polo, unpublished).The sculpted limestone object is nearly complete and represents a local product for which three possible quarries, located close to Briord, may be considered as sources for the material. The sculpture had been carved in a single block. A small piece of the right arm, the end of the legs and the feet are missing. The back of the sculpture is unfinished. Small fractures damage the nose, the left cheek and the chin.The subject depicted by the sculpture is that of a young man, a private citizen, wearing a toga. His face is oval and regular, and is not lined by wrinkles. His short hairstyle corresponds to the fashion of the Julio-Claudian period. The short fringe is paired with small and even locks, which are arranged similarly to hairstyles visible in some portraits of Tiberius and Caligula, during the reign of Tiberius to that of Claudius.The toga depicted by the sculpture presents a number of noteworthy characteristics, including: the hanging strip of cloth, formed by the material flowing from the left shoulder to the right hand. The figure appears to have a pronounced swaying of the hips and there is some corresponding twisting of the pleats below the left hand. This toga, without umbo, retains, in its overall shape, certain features of the Roman toga dating to the 1st c. BC. The separate swathe of cloth held by the right hand of the sculpted individual, however, represents a rare feature. A Julio-Claudian togatus discovered in Barcino is a close comparison. Indeed, the Roman toga of Briord is halfway between the new trends of its period and the old Italic influences. New research into the beginning of the 1st c. AD, will provide insight into toga trends of the Early Roman Empire.This local sculpture, likely belonging to a funerary monument, is now a major piece by virtue of its unique feature and fine quality in the study of the sculpture in Gaul during the Tiberius-Claudius period.